Analysis of Stunting Management Policy : Case of Pandeglang, Banten - Indonesia - Ricca Handayani; Sri Rahayu (PT FORMOSA CENDEKIA GLOBAL, 2023)
Stunting is still a global problem, including Indonesia. Indonesia, which is ranked 4th in the world rankings and 2nd in Southeast Asia, is of particular concern to many parties. This study aims to identify problems and analyze the regional government's policy strategy for dealing with stunting in the Pandegelang - Banten area, which is the district with the highest prevalence of stunting under-fives. This study used a qualitative research design with data collection based on a desk study using secondary data, publications and other research reports. The results of this study refer to the development of the Edward III model adopted in previous studies and conclude that based on the criteria of the Edward III model, the policies that are planned and implemented are appropriate and appropriate, although there are weaknesses and some obstacles in their implementation. The renewal of this research is the focus on the policy of the Pandegelang regional government which is the area with the highest stunting rate in Banten province.